‘Out of the Tropics’ Sheds Light on Latitudinal Gradients in Clade Ages of Climbers, China - Mingfei Zhao; Hongbo Li; Yuhang Wang; Yuan Jiang; Muyi Kang; Kaixiong Xing (Ecology and Evolution, 2025)
ABSTRACT We aim to test hypotheses on the patterns of clade age of climbing plants under climatic variations along the latitudinal gradients in China. Specifically, we uncover their general patterns of mean family age (MFA) and their climatic drivers. We evaluate the extents to which both the tropical niche conservatism hypothesis (TNC) and the out of the tropics hypothesis (OTT) can account for the MFA of climbing plants, respectively. A dataset including 2487 climbing species was used to quantify geographical patterns of MFA across China. Spatial regression analyses with information‐theoretical multi‐model selections were performed to estimate the importance of climatic variables. There were generally increasing trends of MFA from low to high latitudes for all types of climbers. For woody climbers, MFA was negatively correlated with minimum temperature and annual mean precipitation but positively correlated with seasonal temperature and precipitation, and was mostly influenced by mean temperature of the coldest quarter. For herbaceous vines, the MFA pattern showed relatively insignificant correlations with all the climatic variables. Our results highlight that the OTT hypothesis offers a promising explanation for the latitudinal MFA gradients of climbers in China (especially for woody climbers), which turn out to be contrary to the TNC predictions.